Increasing Teachers’ Work Engagement Through Servant Leadership, Organizational Culture, and Job Satisfaction - Hidayat, Dylmoon; Maitimo, Vinsensius V. S.; Suwu, Selvi Ester (Universitas Pendidikan Ganesha, 2020)
As an educational institution that teaches Christian values, Christian schools can play a role in building the character of the nation through education and science in accordance with Christian values. For those role it is necessary for the schools to employ committed human resources. Most of previously done research on work engagement involved factors of leadership style and job satisfaction, yet, very few included organizational culture. This research aimed to determine the effect of servant leadership, organizational culture and job satisfaction on work engagement. The research subjects were 63 teachers at junior high and senior high Christian schools located in West Jakarta. The research design used the path analysis through PLS-SEM method. The results showed that the servant leadership and organizational culture have a positive effect on job satisfaction and work engagement, but lacking evidence to prove the job satisfaction effects the work engagement. Therefore, to improve the teachers’ work engagement, one need to pay attention on two key factors: the leadership style that serves from the principal and conducive organizational culture.